The Interaction Between β‐3 Adrenergic Receptor and Peroxisome Proliferator‐Activated Receptor Gamma Gene Polymorphism to Periodontal Disease in Community‐Dwelling Elderly Japanese. Issue 8 (1st August 2015) - Yoshihara, Akihiro; Sugita, Noriko; Iwasaki, Masanori; Wang, Yanming; Miyazaki, Hideo; Yoshie, Hiromasa; Nakamura, Kazutoshi
Abstract : Background: It has been hypothesized that β‐3 adrenergic receptor and peroxisome proliferator‐activated receptor gamma (PPARγ) might have gene–environmental and gene–gene interactions in periodontal disease. The purpose of this study is to elucidate the interaction between β‐3 adrenergic receptor and PPARγ gene polymorphism with periodontal disease. Methods: Three hundred thirty‐two postmenopausal females were enrolled, and their serum high‐sensitivity C‐reactive protein (hsCRP) and hemoglobin A1c (HbA1c) were examined. β‐3 adrenergic receptor and PPARγ genotypes were then determined. An oral examination was performed. The number of remaining teeth was counted, and the probing depth (PD) and clinical attachment level (CAL) were measured. Prevalence‐rate ratios (PRRs) were calculated by multiple Poisson regression analyses to evaluate the relationship among periodontal disease markers, such as the number of sites with CAL 4 to 5 or ≥6 mm or PD 4 to 5 or ≥6 mm, and β‐3 adrenergic receptor polymorphisms, PPARγ polymorphisms, and the interaction term adjusted by age, hsCRP, and HbA1c, after converting the number of remaining teeth (n) to an offset variable. Results: In the participants with body mass index (BMI) ≥25, PRRs of β‐3 adrenergic receptor genotype (Trp/Arg and Arg/Arg) for periodontal disease markers were 0.13 to 0.70 ( P <0.0001 to 0.74), those of PPARγ genotype (Pro/Pro) were 0.66 to 3.14 ( P = 0.01 to 0.68), and those of the interaction term for the two genotypes were 1.69 to 12.61 ( P <0.0001 to 0.33). However, in the participants with BMI <25, a constant tendency was not observed. Conclusion: The results confirmed a positive relationship between the interaction term for β‐3 adrenergic receptor genotype and PPARγ genotype and various periodontal markers in obese elderly females.